Hyperspectral multi-indicator ripeness perception model for mechanized harvesting of “Yulu Xiang” pears - Na Ma; Jinyan Sun; Yingjun Li; Shijun Sun; Chenfei Li; Yile Sun; Zonglin Liu; Wendong Niu; Xiaoqin Xue; Haiyan Song (Computers and Electronics in Agriculture, 2026)

Hydrological dynamics regulate reactive oxygen species production in the largest freshwater lake of China - Wenkang Li; Siwen Li; Dinggui Wu; Chaoran Guo; Huacheng Xu; Na Song (Water Research, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Matrix effects of tartaric acid on the volatile release and aroma perception of fruity esters in wine - Fan Feng; Na Li; Hongcong Song; Aihua Li; Yongsheng Tao (Food Research International, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

Intranasal BCG cell wall polysaccharide-based subunit vaccine confers protection against Mycobacterium bovis challenge in mice - Na Li; Mengting Zhou; Yinjuan Song; Li Tang; Hui Ma; Jian Xu; Jian Cao; Na Li; Yuefeng Chu (Veterinary Microbiology, 2026)

Regulation of mycelium–egg white protein composite formation by pH and ionic strength - Mukadaisi Muhedaner; Ziqing Song; Na Huang; Mengjun Li; Guanghong Zhou; Keping Ye (Food Bioscience, 2026)

Photodegradation process of microplastics mediated by biochar-derived dissolved organic matter: Insights from density functional theory calculations - Kunliang Jiang; Zaifeng Wang; Huacheng Xu; Zhaoliang Peng; Yuxuan Zhang; Wenkang Li; Shengkai Zhou; Qingru Wan; Na Song (Chemical Engineering Journal, 2026)

Mechanistic review of binary to ternary starch-biomolecule assemblies: Integrated insights into resistant starch formation and structure-function relationships - Jiaqi Song; Chunmin Ma; Yue Xu; Xinyu Xu; Jiawang Wang; Lulu Li; Guang Zhang; Bing Wang; Yang Yang; Na Zhang (Carbohydrate Polymers, 2026)

A reference-guided large language model workflow for mobile phase selection in thin-layer chromatography enabled by a polarity-space tetrahedron strategy - Wei-Song Kong; Song-Xue Shao; Li-Na Zhu; Xi Yu (Analytica Chimica Acta, 2026)

Biochar enhances soil carbon in iron-rich red soil but fails in calcareous fluvo-aquic soil: Mineral protection outweighs microbial turnover - Wanyi Fang; Peipei Li; Ge Song; Na Deng; Siyi Liu; Tianran Sun; Limei Zhang (Agriculture, Ecosystems & Environment, 2026)

Early-stage targeted low-dose chlorine-bentonite treatment for cyanobacterial bloom control in deep reservoirs - Xi Li; Shengda Wang; Weijun Song; Bastiaan W. Ibelings; Yiruo Xia; Miquel Lürling; Nesrine Imene Hame; Hichem Nasri; Viktor A. Gabyshev; Andrey Yu. Krasnopeev; Olga I. Belykh; Na Lin; et al. (Journal of Hazardous Materials, 2026)

Metabolomic insights into flavonoid migration and bioactivity enhancement in Apocynum venetum tea during hot-water brewing - Syeda Wajeeha Gillani; Kuo Xu; Ping Li; Xueli Lu; Bo Wang; Lu Wang; Juying Wang; Guosheng Wang; Ruolin Song; Tingting Ren; Chen Meng; Yiqiang Li; et al. (Food Chemistry, 2026)

A novel sandwich immunoassay for Staphylococcus aureus using horseradish peroxidase-conjugated trivalent nanobody - Na Su; Chunxu Yang; Lei Zhu; Heyang Song; Tuyatsetseg Jambal; Li Yi; Rimutu Ji (Food Chemistry, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

One-dimensional chain structure enables anisotropic hard X-ray detection in Hg2Br2 single crystal with ultralow detection limit - Lin Liu; Yunqiu Hua; Qi Li; Tao Wang; Na Lin; Zhongjie Yue; Jian Song; Zhitai Jia; Xian Zhao; Guodong Zhang; Xutang Tao (Chemical Engineering Journal, 2026)

Multiphysics CFD analysis of packed bed adsorption of Ni(II) using MnO2-modified Hypericum rhizome-derived biochar: Batch and column approaches - Sheng Qian; Xiang Ao; Wei Zhang; Chenhao Song; Kaihong Wen; Dona Souliyathai; Xingyong Li; Na Liu; Liping Ma; Longlong Ma; Shijie Liu; Yubao Chen (Biomass and Bioenergy, 2026)

Selective suppression of key hazardous asphalt VOCs by MIL-101: From risk screening to mechanistic insights - Jinyi Wu; Na Li; Habib Ullah; Zakir Zaman Khan; Jianlin Feng; Yu Song; Quantao Liu; Shaopeng Wu; Jianying Yu (Journal of Cleaner Production, 2026)

Biotransformation of 2-Aminobenzothiazole by a newly isolated Rhodococcus sp. YQ-4 eliminates its toxicity to sensitive organisms - Fuyu Song; Jiaxi Liu; Qi Wu; Aiqin Diao; Yinhu Jiang; Xin Yan; Na Li; Jian He; Jiguo Qiu (International Biodeterioration & Biodegradation, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

Dual covalent–hydrogen-bond networks enable synergistic thermo-mechanical performance and durability in polyimide films - Luling He; Xiong Li; Jiamei Liu; Yu Zhang; Na Song; Tongle Xu; Peng Ding (Chemical Engineering Journal, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

PFOS promotes Alzheimer’s disease through aggravating the cell apoptosis and AKT/GSK3β/NF-κB/NLRP3 pathway mediated inflammation - Ming Li; Xianhao Ping; Huixin Song; Jin Sun; Qian Yang; Li-Na Gao (Toxicology, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Effects of cadmium-tolerant bacteria combined with biochar on cadmium and selenium dynamics in rice grown on seleniferous soils: Insights from a soil bacterial community analysis - Yanan Cheng; Jing Jiang; Lanping Song; Shangqi Xu; Meng Na; Kun Cheng; Daming Li; Shoubiao Zhou; Jihai Zhou (Journal of Environmental Chemical Engineering, 2026)

Superhydrophilic and underwater superoleophobic chitin nanocrystals/ palygorskite nanoclays membrane for multifunctional oil/water emulsion separation - Chenglong Wang; Chenglan Zhang; Jiajie Li; Chun Song; Chenchen Lu; Chenxin Guo; Chunyu Chang; Bo Duan; Na Peng (Journal of Environmental Chemical Engineering, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Functional trait variation of Rhododendron aureum in relation to Deyeuxia angustifolia encroachment in an alpine tundra - Na Li; Zhaoyong Hu; Guangqi Zhang; Mai-He Li; Zhengfang Wu; Renkai Dong; Suke Hou; Chao Song; Haibo Du (Plant and Soil, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Validation and Correction of In-Orbit Tangent Height for the Ozone Monitoring Suite-Limb onboard FY-3F - Song Liu; Yuan Li; Na Xu; Lin Chen; Peng Zhang; Minzheng Duan; Yapeng Wang; Jiachen Wang; Ruonan Jiang (Journal of Meteorological Research, 2026)

Characterization of novel Vibrio parahaemolyticus JD2305 and comparative genomics of the Tc toxin mobilome in Vibrio pathogens associated with translucent postlarvae disease - Laizhuang Jin; Na Ying; Qianhui Song; Liguo Yang; Letian Li; Lei Feng; Hui Zhang; Mao Lin; Xinshu Li; Wenhong Fang (Aquaculture, 2026)

Pore architecture reshaping and microbial network restructuring drive sunflower yield gains in saline-alkali soil via straw-sand interlayer systems - Xiaolong Bai; Na Liu; Jie Zhou; Jiashen Song; Guoli Wang; Aiping Chen; Yongliang Chen; Jing Wang; Hongyuan Zhang; Yuyi Li (Soil and Tillage Research, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Single-nucleus RNA sequencing reveals the underlying roadmap of early gonadal differentiation in teleost - Jialin Wang; Yajuan Huang; Zhongkai Cui; Kaili Zhang; Na Wang; Jun Luo; Yu Song; Bowen Hu; Ming Li; Yadong Chen; Manfred Schartl; Songlin Chen (Science China Life Sciences, 2026)

Physiological and molecular responses to sodium acetate addition and supplementation in the two stages of Haematococcus pluvialis - Yanbin Li; Weizhao Han; Na Li; Tian Xie; Xin Tan; Song Tang; Yequan Sheng; Bangxiang He (Journal of Oceanology and Limnology, 2026)

Analysis of the antibacterial activity and mechanism of Litsea cubeba essential oil against Vibrio parahaemolyticus JD2305 causing translucent postlarvae disease - Qianhui Song; Laizhuang Jin; Di Fang; Na Ying; Lei Feng; Letian Li; Xiong Zou; Wenhong Fang (Aquaculture, 2026)

Millennial- to centennial-scale record of organic carbon accumulation and its periodic occurrence in the Yellow Sea since the last deglaciation - Yuying Zhang; Limin Hu; Yazhi Bai; Lina Jin; Hyung Jeek Kim; Na Li; Song Zhao; Jun Ye; Yonghua Wu; Xiao Wu; Xiting Liu; Xun Gong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

A DAMP- and antigen-capturing nanosponge designed as personalized cancer vaccine - Ting Meng; Weikai Sun; Chuanning Wang; Han Yang; Yafei Qi; Daqian Sun; Bingrun Song; Bingzhao Li; Aixin Song; Na Sun; Zhiliang Gao; Dexin Yu (Chemical Engineering Journal, 2026)

Evaluation and forecast of the regional marine innovation ecosystem’s competitiveness: A systematic multivariate grey interval model with spatial proximity effects - Xuemei Li; Na Li; Song Ding (Journal of Geographical Sciences, 2026)

The WRKY Transcription Factor SbWRKY51 Positively Regulates Salt Tolerance of Sorghum - Xuemei Wang; Hao Li; Jingyi Wang; Jie Song; Na Sui (Plant Science, 2026)

Genome analysis and secondary metabolite characterization of Bacillus velezensis JZ as a potential biocontrol agent - Li Zhang; Lizhu Shao; Boyuan Zhang; Yuting Li; Ziyu Wang; Shuhong Song; Miaomiao Yang; Boshen Wang; Dandan Zhai; Na Liu; Peng Li (Physiological and Molecular Plant Pathology, 2026)

Transcriptomics, 16S rDNA, and metabolomics reveal Alhagi honey polysaccharides alleviating alcoholic liver disease via gut-liver axis - Jianzhong Song; Xin Zhao; Zhiyuan Lv; Jinfa Li; Na Mi; Junmin Chang; Xiumin Ma (Food Bioscience, 2026)

The (-)-endo-fenchol synthases from three species of lavender: predicted structural models and multilevel regulation of gene expression - Dafeng Liu; Na Li; Huashui Deng; Hongying Song; Mengjiao Cao; Xueying Miao; Minawaier Maimaiti; Kailibinuer Aili; Kejia Qian (Physiology and Molecular Biology of Plants, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

EphA/EphrinA5 signaling pathway involved in the abnormal synaptic remodeling and neurotoxicity caused by benzo[a]pyrene - Xin Li; Shuang Zhou; Xiaoling Zhou; Jinfeng Zhang; Na Xia; Yangyang Li; Zhanfei Song; Hongmei Zhang (NeuroToxicology, 2025)

Characterization and risk prioritization of PFAS via nontarget screening in soil and maize near a fluoropolymer manufacturing facility - Xiaotong Li; Na Li; Ru-song Zhao; Yali Shi; Yaqi Cai (Journal of Hazardous Materials, 2025)

Multidimensional strategy for discovering saltiness-enhancing peptides in shrimp heads integrating ultra-high pressure hydrolysis and machine learning - Na Li; Yafang Song; Yang Liu; Rong Liu; Yahong Li; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Coral-like cobalt/nitrogen-doped porous carbon synergized with MnO₂ for ultrasensitive electrochemical detection of luteolin in floral teas - Yafeng Jin; Fangming Han; Didi Tong; Xinyue Song; Di Wang; Tao Wang; Xiangquan Qin; Na Chen; Xiaobo Li; Guangri Xu (Food Chemistry, 2025)

Lignin nanoparticles mediated self-adhesive and conductive hydrogel electrolytes for high-performance flexible supercapacitors - Jiabin Han; Yuxin Song; Jiangbo Li; Bing Wang; Jian Zhang; Shuyi Li; Xingwen Wang; Na Li; Xueru Sheng; Haiqiang Shi; Changyou Shao; Runcang Sun (Chemical Engineering Journal, 2025)

In situ fabrication of bacterial cellulose-based CB@Poly(ionic liquid) membranes via surfactant-free ionic liquid microemulsion: Enhanced conductivity and mechanical flexibility - Na Gao; Caiyang Zhang; Minxin Song; Jiaxing Fan; Jinyue Li; Shunjie Li; Nan Lou; Guangshun Wu; Yuyang Liu; Jian Xue; Aili Wang (Carbohydrate Polymers, 2025)

Transcriptome and physiological analysis revealed core genes that promote glutathione metabolism in blue honeysuckle in response to freezing stress - Yuxin Fan; Dandan Zang; Tianyi Wang; Zhihua Song; Na Li; Hongyan Cao; Tingting Du; Meng Qi; Yujie Fu; Qing Yang; Biying Dong; Dong Meng (Tree Genetics & Genomes, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Jaagichlorella menglunensis sp. nov. (Watanabeales, Chlorophyta), a new coccoid green alga isolated from China - Huiyin Song; Rongli Guan; Tian He; Langyue Zhang; Tiantian Li; Junfei Zhou; Yuxin Hu; Shuyin Li; Feng Liu; Lun Li; Na Zhang; Huafeng Xiao; et al. (Journal of Oceanology and Limnology, 2025)

Experimental research on citric acid modified magnesium oxysulfate cement composites under dry-wet cycles: Mechanical properties and microscopic mechanism - Na Li; Yifang Song; Wei Wang; Ping Jiang; Xinyu Yan; Jun Zhang; Guoxiong Mei (Sustainable Chemistry and Pharmacy, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Scalable and fast electrophoresis-accelerated assembly of chiroptical carbon fibers with multi functions - Haixing Jiao; Baiqi Song; Fa Li; Yuanhan Tang; Na Zhang; Xiaofang Zhang; Weilin Xu (Chemical Engineering Journal, 2025)

Association of Breast Cancer and Selective Estrogen Receptor Modulators on the Risk of Meningioma: Insights from Mendelian Randomization - Youjia Qiu; Minjia Xie; Bingyi Song; Menghan Wang; Na Ji; Ziqian Yin; Jinglin Li; Xinling Tang; Chao Ma; Zhong Wang (Molecular Neurobiology, 2025)

The Reorganization of Subcortical Network Reflects Sensory-Motor Abilities in Patients after Spinal Cord Injury - Na Li; Meisi Song; Mao Pang; Xiaodan Ma; Weihong Qiu; Zhuang Kang; Yong Yu; Zhaocong Chen; Zulin Dou; Xiquan Hu; Bin Liu; Limin Rong (Brain Topography, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

The growth and nutrient removal properties of a newly isolated Desmodesmus sp. XNY-2104 under mixotrophic and heterotrophic conditions using volatile fatty acids (VFAs) - Jie Li; Na Liu; Wenbao Yan; Qi Zhao; Xinglong Zhou; Cong Jia; Chongqing Xu; Xiaozhe Song; Mingming Song (Biomass and Bioenergy, 2025)

GALM Alleviates Aβ Pathology and Cognitive Deficit Through Increasing ADAM10 Maturation in a Mouse Model of Alzheimer’s Disease - Na Tian; Junjie Li; Xiuyu Shi; Mingliang Xu; Qian Xiao; Qiuyun Tian; Mulan Chen; Weihong Song; Yehong Du; Zhifang Dong (Neuroscience Bulletin, 2025)

Salidroside alleviates cardiomyocyte senescence by activating the AMPK-mediated signaling pathway - Lan Zhang; Yawei Liu; Zhijuan Hua; Yan Qin; Tao Wang; Na Li; Lei Song (Journal of Molecular Histology, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Mitigating the impacts of ionospheric irregularities on GPS precise positioning by refined cycle slip threshold - Wei Li; Shuli Song; Tianyang Bai; Na Cheng; Weili Zhou; Chao Yu (GPS Solutions, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Discovery of isopentenyl flavonoids with inhibitory activity against hepatocellular carcinoma cells based on DeepSAT - Qing Wang; Ben‐Song Xin; Wen-Long Kou; Li-Na Gao; Gu-Xue Zhang; Yan-Jiao Qiao; Guo‐Dong Yao; Xiao‐Xiao Huang; Shao‐Jiang Song (Phytochemistry, 2025)

Enhanced pH-universal hydrogen evolution reactions on the Rh/MoO3 electrocatalysts - Jiaxin Yuan; Jianrui Feng; Gang Li; Yinghao Song; Na Yu; Xi Chen; Guanjie He; Yeshu Tan; Meng Ni (Chemical Engineering Journal, 2025)

Dual-site pinning engineering in O3-type layered oxides cathode materials for high-performance sodium-ion batteries - Zixuan Huang; Hongyi Wang; Shilong Li; Rongzheng Tian; Kai Liu; Hongzhou Zhang; Shiqiang Liu; Xixi Shi; Na Zhang; Dawei Song; Lianqi Zhang (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Effects of hypoxic stress on gastric sieve (GS) filtering function of Litopenaeus vannamei - Letian Li; Yuan Wang; Laizhuang Jin; Lei Feng; Qianhui Song; Di Fang; Na Ying; Xincang Li; Wenhong Fang (Aquaculture, 2025)

Impact of ibuprofen on nitrogen removal performance and its biotransformation in a coupled sulfur autotrophic denitrification and anammox system - Qiong Wang; Yuqi Li; Na Chen; Xiaojing Zhang; Yongpeng Ma; Yali Song (Journal of Hazardous Materials, 2025)

An extensin-like gene OsPEX1 plays key roles in temperature stress response in rice - Jieni Li; Ao Li; Yue Wang; Zhi-Hao Wu; Xiaohong Li; Jie Meng; Chen Liang; Yuxin Song; Na Liu; Wanzhen Gao; Haifeng Peng; Yingxue Yang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Immunofluorescent analysis of exosomes using a microchip filled with transparent antibody-conjugated beads for breast cancer liquid biopsy - Na Li; Cheng Cheng; Di Wu; Zixuan Song; Bei Wang; Guiying Li; Fang Yang (Analytica Chimica Acta, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Regional high iron deposition on brain quantitative susceptibility mapping correlates with cognitive decline in chronic kidney disease patients - Yuan Li; Yuhan Jiang; Bingbing Gao; Na Liu; Yukun Zhang; Huiling Zhou; Qingwei Song; Nan Wang; Yanwei Miao (Brain Imaging and Behavior, 2025)

The growth and nutrient removal properties of heterotrophic microalgae using volatile fatty acids under different nitrogen forms and its application in actual acid-producing wastewater - Cong Jia; Na Liu; Lei Chen; Wenbao Yan; Qi Zhao; Jie Li; Ze Yu; Mingming Song; Chongqing Xu; Xiaozhe Song (Journal of Environmental Chemical Engineering, 2025)

A novel 0D/2D heterojunction Bi2Sn2O7/BiOCOOH with BiOCOOH nanosheets as support for the boosted photodegradation of tetracycline: The role of BiOCOOH in the photogenerated electron transfer - Shuo Han; Fangyan Chen; Yubin Tang; Wenqian Sun; Yanhua Song; Kaiwen Zhang; Na Li (Journal of Environmental Chemical Engineering, 2025)

Characterization of the effects of bridging linker on the β-Lactoglobulin binding mechanism on the nanoscale metal-organic frameworks - Na Gan; Yali Song; Yilin Li; Peiran Liu; Si Chen; Yi He; Tingting Zeng; Wei Wang; Di Wu (Food Chemistry, 2025)

Using multi-modal spectroscopy technology and microscopic analysis to explore the regulation of ultra-high pressure heat-assisted treatment on the texture of ready-to-eat shrimp during storage - Na Li; Zhifeng Tan; Ruida Ma; Yafang Song; Rong Liu; Jiaxin Zhao; Ningbo Qin; Yahong Li; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Allicin amplifies disulfidptosis during GOx catalyzing glucose-starvation for cancer therapy via simultaneous antimicrobial and antitumor intervention - Taotao Huo; Bin Zhu; Xiaoyu Shan; Jiaqi Song; Ziyi Wang; Jianxu Zhou; Xianpeng Zhang; Yuquan Bai; Chengcheng Liu; Yiyang Zhao; Na Mei; Yazhong Bu; et al. (Chemical Engineering Journal, 2025)

Conductive, adhesive, and biocompatible hydrogel sensor based on zwitterionic for effective wound healing and monitoring - Meng Wei; Haihua Wang; Chaoxian Chen; Guiqiang Fei; Dong Yang; Ke Li; Mengxi Wang; Xin Yang; Na Li; Ling Song; Mengfan Yang; Zhigao Wang (Chemical Engineering Journal, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Rice rhizosphere microbiome is more diverse but less variable along environmental gradients compared to bulk soil - Yaping Guo; Yakov Kuzyakov; Na Li; Bin Song; Zihao Liu; Jonathan M. Adams; Lin Yang (Plant and Soil, 2025)

Navβ2 Intracellular Fragments Contribute to Aβ1-42-Induced Cognitive Impairment and Synaptic Deficit Through Transcriptional Suppression of BDNF - Min-Nan Lu; Dan Wang; Chen-Jun Ye; Guo-Ji Yan; Jing-Feng Song; Xin-Ying Shi; Shan-Shan Li; Li-Na Liu; Hui-Xiang Zhang; Xiao-Han Dong; Tao Hu; Xu-Yang Wang; et al. (Molecular Neurobiology, 2025)

The substantial generation of photochemically produced reactive intermediates (PPRIs) in algae-type zones from one large shallow lake promoted the removal of organic pollutants - Wenkang Li; Weidong Jin; Dinggui Wu; Chunliu Wang; Huacheng Xu; Na Song (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Mycoplasma bovis activates apoptotic caspases to suppress xenophagy for its intracellular survival - Yinjuan Song; Li Tang; Na Li; Jian Xu; Zhengyang Zhang; Hui Ma; Yi Liao; Yuefeng Chu (Veterinary Microbiology, 2024)

Drinking water safety improvement and future challenge of lakes and reservoirs - Yunlin Zhang; Jianming Deng; Yongqiang Zhou; Yibo Zhang; Boqiang Qin; Chunqiao Song; Kun Shi; Guangwei Zhu; Xuejiao Hou; Yinjun Zhang; Shiwen He; R. Iestyn Woolway; et al. (Science Bulletin, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Hydroxyl radicals dominated the reduction of antibiotic resistance genes by inactivating Gram-negative bacteria during soil electrokinetic treatment - Binxu Li; Kaiyang Jiang; Tingting Song; Mengmeng Yan; Na Li; Zhenzhen Yang; Changxiong Zhu; Hongna Li (Journal of Environmental Management, 2024)

Comprehensive evaluation and screening of saline–alkali tolerant Japonica rice accessions during the whole growth stage - Chengbin Qiao; Kairong Duan; Jiawei Song; Zilan Jiao; Min Chen; Yue Dong; Jingwen Wang; Shuaiguo Ma; Na Wang; Chengke Luo; Peifu Li; Lei Tian (Euphytica, 2024)

Efficient adsorption of short-chain perfluoroalkyl substances by pristine and Fe/Cu-loaded reed straw biochars - Na Liu; Yinhui Li; Minggu Zhang; Naiju Che; Xianliang Song; Yanli Liu; Chengliang Li (Science of The Total Environment, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

IRF9 and STAT1 as biomarkers involved in T-cell immunity in atherosclerosis - Wei Xie; Xiang Gao; Liang Zhao; Shifei Song; Na Li; Junming Liu (Journal of Biosciences, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

The monokaryotic filamentous fungus Ustilago sp. HFJ311 promotes plant growth and reduces Cd accumulation by enhancing Fe transportation and auxin biosynthesis - Shengwang Wang; Xiaofan Na; Meiyun Pu; Yanfang Song; Junjie Li; Kaile Li; Zhenyu Cheng; Xiaoqi He; Chuanji Zhang; Cuifang Liang; Xiaomin Wang; Yurong Bi (Journal of Hazardous Materials, 2024)

Relationship between resistivity and physical properties of seafloor sediments in the hydrate production test area of the South China Sea - Zhiwen Sun; Yiping Miao; Zhihan Fan; Xiaoshuai Song; Liang Xue; Na Zhu; Xianming Zhu; Xiaomeng Li; Yue Qiao; Zhongqiang Sun; Kai Li; Yanlong Li; et al. (Marine Georesources & Geotechnology, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Structural variations of a new fertility restorer gene, Rf20, underlie the restoration of wild abortive-type cytoplasmic male sterility in rice - Shufeng Song; Yixing Li; Mudan Qiu; Na Xu; Bin Li; Longhui Zhang; Lei Li; Weijun Chen; Jinglei Li; Tiankang Wang; Yingxin Qiu; Mengmeng Gong; et al. (Molecular Plant, 2024)

Dynamic variation in the aroma characteristics of Rhus chinensis honey at different stages after capping - Hongxia Li; Yaning Lang; Zhaolong Liu; Mei Song; Ao Jiang; Na Li; Lanzhen Chen (Food Chemistry, 2024)

Multi-component Crystal Strategy for Improving Water Solubility and Antifungal Activity of Climbazole - Wenxi Song; Na Wang; Ao Li; Xiongtao Ji; Xin Huang; Ting Wang; Hongxun Hao (Pharmaceutical Research, 2024)

Exploring the Roles of m6A-Modified circRNAs in Myasthenia Gravis Based on Multi-Omics Analysis - Shuang Li; Yu Zhang; Geyu Liu; Na Song; Zhe Ruan; Rongjing Guo; Yonglan Tang; Xiangqi Cao; Xiaoxi Huang; Ting Gao; Sijia Hao; Qingqing Wang; et al. (Molecular Neurobiology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Phosphatidylserine and/or Sialic Acid Modified Liposomes Increase Uptake by Tumor-associated Macrophages and Enhance the Anti-tumor Effect - Zihan Xu; Jie Li; Na Yan; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2024)

Nitrogen dynamics of alpine swamp meadows are less responsive to climate warming than that of alpine meadows - Xiaopeng Chen; Genxu Wang; Na Li; Ruiying Chang; Tao Zhang; Tianxu Mao; Chunlin Song; Kewei Huang (Science of The Total Environment, 2024)

Delaying crystallization and anchoring the grain boundaries defects via π-π stacked molecules for efficient and stable wide-bandgap perovskite solar cells - Jinliang Shen; Na Li; Yuhang Wang; Xiang Ge; Junlei Tao; Song Yin; Xingkun Ning; Tingwei He; Guangsheng Fu; Shaopeng Yang (Chemical Engineering Journal, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

In-situ precipitation zero-valent Co on Co2VO4 to activate oxygen vacancies and enhance bimetallic ions redox for efficient detection toward Hg(II) - Zhi-Wei Gao; Hao Li; Pei-Hua Li; Yong-Yu Li; Jia-Qing Quan; Na Ma; Shi-Hua Chen; Xing-Jiu Huang; Zong-Yin Song; Meng Yang (Analytica Chimica Acta, 2024)

Minimizing environment footprint through half-plastic film mulch and straw incorporation in maize-based system - Jinze Bai; Danyang Chen; Zhihao Zhang; Yuming Huang; Yuxin Bai; Jiaqi Hao; Jiajie Song; Na Li; Guangxin Ren; Xiaojiao Wang; Gaihe Yang; Sudhir Yadav; et al. (Agriculture, Ecosystems & Environment, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Two new degrade triterpenoids from Buxus bodinieri Levl. - Yu-Xin Yan; Na-Li Song; Ji-Hong Zhang; Ming-Hua Qiu (Natural Product Research, 2024)

Advancement of foodomics techniques for honey botanical origins authentication: Past decade (2013–2023) and future perspectives - Na Li; Mei Song; Hongxia Li; Zhaolong Liu; Ao Jiang; Yaning Lang; Lanzhen Chen (Trends in Food Science & Technology, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Crosstalk between autophagy and inflammasomes in ricin-induced inflammatory injury - Shiji Zhang; Na Zhao; Suli Song; Yanchun Wang; Yan Wang; Chengbiao Sun; Mingxin Dong; Mengqi Huo; Na Xu; Wensen Liu; Guorui Li (Toxicology and Applied Pharmacology, 2024)

Mechanical properties and constitutive model of high-abundance methane hydrates containing clayey–silt sediments - Fan Yang; Changjun Li; Na Wei; Wenlong Jia; Jie He; Shuoshuo Song; Yuanrui Zhang; Youzhi Lin (Ocean Engineering, 2024)

Preparation and properties of hydrophobic materials based on environmentally responsive low fluorine epoxy copolymer - Chengmin Hou; Weimin Yan; Na Li; Jiaqi Song; Qianqian Liao; Kexin Li; Qianruo Chen; Qi Gui (Journal of Environmental Chemical Engineering, 2024)

Study on small strain characteristics and microscopic mechanism of rice husk ash modified lime soil - Na Li; Shimeng Yu; Erlu Wu; Xinjiang Song; Ping Jiang; Haibo Xu; Wei Wang (Transportation Geotechnics, 2024)

How does industrial transformative process shape the spatial dynamics of urban development? - Weize Song; Wenqing Yang; Na Wang; Can Wang; Zheng Li; Yifu Ou; Xiaoling Zhang (Land Use Policy, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Development of an ontology for construction carbon emission tracking and evaluation - Yujie Lu; Guanghan Song; Peixian Li; Na Wang (Journal of Cleaner Production, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Dual-pathway glycolysis inhibition for boosting bioenergetic therapy synergistic with chemodynamic/photothermal therapy - Pengxin Song; Renlu Han; Yun Gao; Zhen Guo; Xiangjun Wei; Na Li; Jiancheng Yu; Keqi Tang (Chemical Engineering Journal, 2024)

Stochastic processes dominated the soil bacterial community assemblages along an altitudinal gradient in boreal forests - Li Ji; Song Sheng; Fangyuan Shen; Lili Yang; Shizhi Wen; Gongxiu He; Na Wang; Xu Wang; Lixue Yang (CATENA, 2024)

Pharmacokinetic interactions between tacrolimus and Wuzhi capsule in liver transplant recipients: Genetic polymorphisms affect the drug interaction - Siqi Huang; Wei Song; Shuangmiao Jiang; Yuanchen Li; Min Wang; Na Yang; Huaijun Zhu (Chemico-Biological Interactions, 2024)

Pivotal Role of GSTO2 in Ferroptotic Neuronal Injury After Intracerebral Hemorrhage - Li Lin; Xiao-Na Li; Zhen-Yan Xie; Yong-Zhen Hu; Qing-Shan Long; Yi-Qi Wen; Xiao-Bing Wei; Li-Yang Zhang; Xue-Song Li (Journal of Molecular Neuroscience, 2024)
Previous research has found that an adaptive response to ferroptosis involving glutathione peroxidase 4 (GPX4) is triggered after intracerebral hemorrhage. However, little is known about the mechanisms underlying adaptive responses to ferroptosis. To explore the mechanisms underlying adaptive responses to ferroptosis after intracerebral hemorrhage, we used hemin-treated HT22 cells to mimic brain injury after hemorrhagic stroke in vitro to evaluate the antioxidant enzymes and performed bioinformatics analysis based on the mRNA sequencing data. Further, we determined the expression of GSTO2 in hemin-treated hippocampal neurons and in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH) by using Western blot. After hemin treatment, the antioxidant enzymes GPX4, Nrf2, and glutathione (GSH) were upregulated, suggesting that an adaptive response to ferroptosis was triggered. Furthermore, we performed mRNA sequencing to explore the underlying mechanism, and the results showed that 2234 genes were differentially expressed. Among these, ten genes related to ferroptosis (Acsl1, Ftl1, Gclc, Gclm, Hmox1, Map1lc3b, Slc7a11, Slc40a1, Tfrc, and Slc39a14) were altered after hemin treatment. In addition, analysis of the data retrieved from the GO database for the ten targeted genes showed that 20 items on biological processes, 17 items on cellular components, and 19 items on molecular functions were significantly enriched. Based on the GO data, we performed GSEA and found that the glutathione metabolic process was significantly enriched in the hemin phenotype. Notably, the expression of glutathione S-transferase omega (GSTO2), which is involved in glutathione metabolism, was decreased after hemin treatment, and overexpression of Gsto2 decreased lipid reactive oxygen species level in hemin-exposed HT22 cells. In addition, the expression of GSTO2 was also decreased in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH). The decreased expression of GSTO2 in the glutathione metabolic process may be involved in ferroptotic neuronal injury following hemorrhagic stroke.

Mechanisms and targeted reversion/prevention of hepatic fibrosis caused by the non-hereditary toxicity of benzo(a)pyrene - Xinru Du; Ming Jin; Ruzhi Li; Fei Zhou; Yuanze Sun; Qinliang Mo; Sisi Song; Na Dong; Shuoke Duan; Maoxuan Li; Ming Lu; Chi Zhang; et al. (Science of The Total Environment, 2024)

Long-term maintenance of high yield and soil fertility with integrated soil-crop system management on the Loess Plateau - Fangfang Zhang; Qilong Song; Tian Ma; Na Gao; Xinkuan Han; Yufang Shen; Shanchao Yue; Shiqing Li (Journal of Environmental Management, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Phosphorus-doped synergy of phase change in heterogeneous catalysts of NiS–NiS2 for efficient electrocatalysis of Pb(II) - Yong-Yu Li; Kai-Yuan Li; Shi-Hua Chen; Na Ma; Zong-Yin Song; Meng Yang; Jie Wang; Wen-Qing Liu (Analytica Chimica Acta, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Evaluation of population genetics of Acanthogobius ommaturus using genotyping by sequencing technology - Chenyu Song; Yuan Li; Na Song (Regional Studies in Marine Science, 2023)

Revolutionizing material design for protonic ceramic fuel cells: Bridging the limitations of conventional experimental screening and machine learning methods - Idris Temitope Bello; Daqin Guan; Na Yu; Zheng Li; Yufei Song; Xi Chen; Siyuan Zhao; Qijiao He; Zongping Shao; Meng Ni (Chemical Engineering Journal, 2023)

Cumulative deformation and non-coaxial characteristics of fiber and cement-modified iron tailings under the rotation of principal stress - Ping Jiang; Zhichao Wang; Na Li; Xinjiang Song; Yewen Chen; Wei Wang (Transportation Geotechnics, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

Investigation and prediction of the biotoxicity of Cu2+ to Chlorella vulgaris: modification of the biotic ligand model - Ming Kong; Zhiqiang Shi; Fei Liu; Na Song; Lizhen Liu; Rongfu Li; Yongming Wu; Huacheng Xu (Environmental Science and Pollution Research, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Oral administration of the herbal oligonucleotide XKC-sRNA-h3 prevents angiotensin II-induced hypertension in mice - Kegong Tang; Xiaona Wang; Yu Zhao; Xiaobei Li; Zhenyu Jiang; Song Mei; Mingrui Chen; Yiming Ma; Xinyi Du; Xiangyu Qiao; Na Sun; Jiaqi Liu; et al. (Science China Life Sciences, 2023)

Genomic Structure and Molecular Characterization of Toll-like Receptors in Black Scraper Thamnaconus Modestus and Their Expression Response to Two Types of Pathogens - Fei Han; Yuan Zhang; Anle Xu; Na Song; Geng Qin; Xiaoyan Wang; Siqing Chen; Li Bian; Tianxiang Gao (Marine Biotechnology, 2023)

BPDE-DNA adduct formation and alterations of mRNA, protein, and DNA methylation of CYP1A1, GSTP1, and GSTM1 induced by benzo[a]pyrene and the intervention of aspirin in mice - Aixiang Liu; Xin Li; Lisha Zhou; Xiaoqing Yan; Na Xia; Zhanfei Song; Jingjing Cao; Zhongsuo Hao; Zhihong Zhang; Ruifeng Liang; Hongmei Zhang (Environmental Science and Pollution Research, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Construction of a food-grade gene editing system based on CRISPR-Cas9 and its application in Lactococcus lactis NZ9000 - Yangping Zhou; Fei Song; Hongru Yang; Dongyao Li; Na Zhang; Kunlun Huang; Xiaoyun He; Miaoshu Wang; Hongtao Tian; Chen Li (Biotechnology Letters, 2023)

Influence of e-waste exposure on DNA damage and DNA methylation in people living near recycling sites - Na Li; Jinhan Wang; Kejun Li; Ping Yang; Yan Wang; Chang Xu; Ningning He; Kaihua Ji; Huijuan Song; Manman Zhang; Liqing Du; Qiang Liu (Environmental Science and Pollution Research, 2023)

Interactions between white and black carbon in water: A case study of concurrent aging of microplastics and biochar - Shi Yao; Ni Ni; Xiaona Li; Na Wang; Yongrong Bian; Xin Jiang; Yang Song; Nanthi S. Bolan; Qiaozhi Zhang; Daniel C.W. Tsang (Water Research, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Metformin alleviates the cognitive impairment induced by benzo[a]pyrene via glucolipid metabolism regulated by FTO/FoxO6 pathway in mice - Tingyi Zhao; Huide Miao; Zhanfei Song; Yangyang Li; Na Xia; Zhiyan Zhang; Hongmei Zhang (Environmental Science and Pollution Research, 2023)

Microbial resistance in rhizosphere hotspots under biodegradable and conventional microplastic amendment: Community and functional sensitivity - Bin Song; Siyi Shang; Feng M. Cai; Zihao Liu; Jie Fang; Na li; Jonathan M. Adams; Bahar S. Razavi (Soil Biology and Biochemistry, 2023)

Graphene/carbon fiber network constructed by co-carbonization strategy for functional integrated polyimide composites with enhanced electromagnetic shielding and thermal conductive properties - Xiong Li; Tongle Xu; Wenjing Cao; Menghuan Wang; Fengqing Chen; Liyuan Jin; Na Song; Sheng Sun; Peng Ding (Chemical Engineering Journal, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Impacts of El Niño–Southern Oscillation on tropical precipitation via triggering anomaly water vapour transport from ocean to land - Jialin Wang; Feifei Pan; Haiyan Li; Pingli An; Guolin Han; Kang Jiang; Xiao Chen; Ziyuan Zhang; Yu Song; Na Huang; Shangqian Ma; Zhenzhen Zhang; et al. (International Journal of Climatology, 2023)
Atmospheric water vapour transport is one of the most active components of the hydrological cycle, which shows great effects on the regional climate variability, while it is largely affected by the large‐scale circulation systems. El Niño–Southern Oscillation (ENSO) shows a remarkable influence on the atmospheric water circulation via disrupting the normal/regular water vapour transport processes, producing the anomaly water vapour fluxes input from ocean to land ( Q net ), and leading to regional precipitation anomalies. However, their quantitative impact has not been fully studied. This study quantified the effect of ENSO on the water vapour transport from ocean to land and identified its impact on tropical precipitation anomalies. The results showed that the global detrended Q net displayed a significantly negative correlation with the strength of ENSO. The notable impact of ENSO on Q net was largely affected by the different patterns of the atmospheric moisture circulation during El Niño and La Niña and was responsible for the change of the spatial distribution of precipitation over the Tropics. El Niño reduced precipitation over the Malay Archipelago and increased precipitation over south China, especially in boreal winter, while La Niña enhanced precipitation over the Malay Archipelago. This study identified the impacts of ENSO on the circulation and water vapour transport process and improved our understanding of the influencing mechanism of ENSO on regional precipitation anomalies, which has important significance on regional water resource management and disaster risk assessment, especially as the extreme climate events have become increasingly frequent.

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Wet-spinning fluorescent alginate fibres achieved by doping PEI modified CPDs for multiple anti-counterfeiting - Li Song; Xiaolan Qiao; Jianxin Sun; Na Yi; Mengyue Wang; Zhihui Zhao; Ruyi Xie; Weichao Chen; Yanzhi Xia (Carbohydrate Polymers, 2023)

A novel endophytic bacterial strain improves potato storage characteristics by degrading glycoalkaloids and regulating microbiota - Fei Song; Chen Li; Na Zhang; Xiaoyun He; Hongru Yang; Ziru Yan; Yangping Zhou; Hongtao Tian; Kunlun Huang (Postharvest Biology and Technology, 2023)

Biochar application reduces residual napropamide in the rhizosphere and improves soil microbial diversity - Ni Ni; Renyong Shi; Qiang Gao; Xiaona Li; Xinyan Guo; Xiaohui Zhang; Mali Shi; Yang Song; Yang Li; Na Wang; Xiaofei Zhang (Biology and Fertility of Soils, 2023)

Modeling Secondary Organic Aerosols in China: State of the Art and Perspectives - Jingyi Li; Haowen Zhang; Lin Li; Fei Ye; Hongli Wang; Song Guo; Na Zhang; Momei Qin; Jianlin Hu (Current Pollution Reports, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

The growth and lipid accumulation of Scenedesmus quadricauda under nitrogen starvation stress during xylose mixotrophic/heterotrophic cultivation - Yiwen Mou; Na Liu; Kunyang Su; Xue Li; Tianxiang Lu; Ze Yu; Mingming Song (Environmental Science and Pollution Research, 2022)

Sensitivity analysis of seismic attributes and oil reservoir predictions based on jointing wells and seismic data – A case study in the Taoerhe Sag, China - Na Li; Jinliang Zhang; Jun Matsushima; Cheng Song; Xuwei Luan; Ming Dou; Tao Chen; Lingling Wang (Frontiers in Marine Science, 2022)
It is important to identify the location of gravelly sandstone in Taoerhe Sag, an oil target area in the Chezhen Depression. To date, most attention has focused on sedimentary characteristics; hence, information regarding a clear sensitivity analysis of seismic attributes is incomplete. To address this, we used well analysis and seismic attribute interpretation to find sensitive seismic attributes and sand bodies. Based on the well analysis and core data, a geologicald model of mudstone and sandstone was established, and the electrical characteristics of three kinds of lithology were identified. We used correlation analysis to select the optimal logging parameters and seismic attributes to identify sandstone. We used multi-attribute fusion technology and stratigraphic slices to characterize the spatial distribution characteristics of gravelly sandstone in the target area and used genetic algorithm inversion volume to evaluate the prediction results. The results indicate that the three main lithologies of the lower submember of Shahejie Formation 3 (P 2 S 3 X ) in the Taoerhe Sag can be distinguished by natural gamma (GR), acoustic time difference (AC) and saturated hydrocarbon content (SH) logging curves. The seismic attribute characteristics of gravelly sandstone of P 2 S 3 X are high root mean square amplitude (RMS) values, high instantaneous bandwidth (BW) values, low 3D curvature (Curv) values, medium-high instantaneous phase (Phase) values and high instantaneous frequency (Freq) values. In this study, we found two nearshore underwater fans in P 2 S 3 X . Gravelly sandstone is located along the slope zone and the lake bottom, with a total sedimentary area of 57.9 km 2 . The method summarized in this paper can be applied to other similar deep-water basins.

Characterization of Chlamydia muridarum TC0668 Protein: Localization, Expression, and Inflammation-Inducing Effects on Host Cell - Na Liu; Xiaofang Li; Hao Chen; Chuan Wang; Wenjing Xiang; Shui Tan; Chenchen Song; Emmanuel Wirekoh Arthur; Asamoah Maxwell; Derrick Annang; Zhou Zhou (Current Microbiology, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Two new sesquiterpenoid lactone derivatives from Lindera aggregata - Song-Song Wen; Yan Wang; Jia-Ping Xu; Qi Liu; Lei Zhang; Jing Zheng; Lin Li; Na Zhang; Xin Liu; Yu-Wen Xu; Zhen-Liang Sun (Natural Product Research, 2022)

Comprehensive insights into the influence of supplemental green light on the photosynthesis of ginger (Zingiber officinale Roscoe) - Xue Lv; Song Gao; Na Li; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Protoplasma, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Transposon insertions within alleles of BnaFT.A2 are associated with seasonal crop type in rapeseed - Qingdong Jin; Gengdong Gao; Chaocheng Guo; Taihua Yang; Ge Li; Jurong Song; Na Zheng; Shuai Yin; Licong Yi; Zhen Li; Xianhong Ge; Graham J. King; et al. (Theoretical and Applied Genetics, 2022)

Transcriptome Analysis of Greenfin Horse-Faced Filefish (Thamnaconus septentrionalis) Gills in Response to Amyloodinium ocellatum (AO) Infection - Li-Guo Yang; Yue Wang; Wen-Bin Xu; Bo Qin; Na Ying; Xue-Feng Song; Yan-Feng Yue; Xiao-Shan Wang; Bian-Bian Zhang; Yan-Qing Wu (Fishes, 2022)
The greenfin horse-faced filefish (Thamnaconus septentrionalis) is susceptible to recurrent Amyloodinium ocellatum (AO) infestation over the grow-out production cycle. This parasite breeds mainly on the gills, causing hypoxia in the fish body, and leading to many deaths. The host-parasite response drives a complex immune reaction, which is poorly understood. To generate a model for host-parasite interaction and the pathogenesis of AO in greenfin horse-faced filefish, an RNA-seq approach, differential gene expression, GO, and KEGG analyses were employed. Overall, 624 new genes and 2076 differentially expressed genes (DEGs) were detected, including 942 upregulated and 1134 downregulated genes in the gills. Compared with the control group, the expression of leptin a, GTPase IMAP family member 4, and NLR family CARD domain-containing protein 3 was significantly higher in the AO-infected group. Conversely, cell wall integrity and stress response component 1-like, and hepcidin-like were significantly downregulated in the gills of AO-infected fish. GO and KEGG enrichment analysis indicated that DEGs were significantly enriched in signaling pathways associated with viral protein interaction with cytokine and cytokine receptor and cytokine–cytokine receptor interaction. Collectively, this transcriptomic study provides novel molecular insights into the pathology caused by AO infestation and alternative theories for future research implementing strategies to control and manage AO.

Occurrence of Phthalate Acid Esters (PAEs) in Protected Agriculture Soils and Implications for Human Health Exposure - Xianxu Li; Na Li; Can Wang; Anyu Wang; Wenjia Kong; Peipei Song; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2022)

SbWRKY55 regulates sorghum response to saline environment by its dual role in abscisic acid signaling - Yushuang Song; Hongxiang Zheng; Yi Sui; Simin Li; Fenghui Wu; Xi Sun; Na Sui (Theoretical and Applied Genetics, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

A superior allele of the wheat gene TaGL3.3-5B, selected in the breeding process, contributes to seed size and weight - Chaojie Wang; Lili Zhang; Yongdun Xie; Xiaofeng Guo; Yanfang Zhang; Yamin Zhang; Ahsan Irshad; Yuting Li; Huihui Qian; Doudou Jing; Guangyao Liu; Kaiming Wu; et al. (Theoretical and Applied Genetics, 2022)

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

SbbHLH85, a bHLH member, modulates resilience to salt stress by regulating root hair growth in sorghum - Yushuang Song; Simin Li; Yi Sui; Hongxiang Zheng; Guoliang Han; Xi Sun; Wenjing Yang; Hailian Wang; Kunyang Zhuang; Fanying Kong; Qingwei Meng; Na Sui (Theoretical and Applied Genetics, 2022)

Design, synthesis, brine shrimp lethality and cytotoxicity of some novel 17a-aza-D-homo-androster-17-one derivatives - Dongfeng Hong; Yiming Ma; Siyao Song; Na Li; Junru Wang (Natural Product Research, 2021)

Different responses of two Chinese cabbage (Brassica rapa L. ssp. pekinensis) cultivars in photosynthetic characteristics and chloroplast ultrastructure to salt and alkali stress - Na Li; Zhihuan Zhang; Song Gao; Yao Lv; Zijing Chen; Bili Cao; Kun Xu (Planta, 2021)

Breast cancer organoids from malignant pleural effusion-derived tumor cells as an individualized medicine platform - Bo Pan; Dongyi Zhao; Yaqian Liu; Na Li; Chen Song; Ning Li; Xuelu Li; Zuowei Zhao (In Vitro Cellular & Developmental Biology - Animal, 2021)

Neighboring tree species alter uptake of NH4+ and NO3− by Chinese fir - Jing Zhou; Qianru Li; Min Liu; Xiaoqi Zhou; Minghua Song; Na Qiao; Huimin Wang; Xingliang Xu (Trees, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Ocean surface current retrieval and imaging with a new shore-based X-band radar based on time-shifted up-and-down linear frequency modulated signal - Yijun He; Xin Song; Baochang Liu; Na Yi; Xiuzhong Li (Acta Oceanologica Sinica, 2021)

Virtual screening of potentially endocrine-disrupting chemicals against nuclear receptors and its application to identify PPARγ-bound fatty acids - Chaitanya K. Jaladanki; Yang He; Li Na Zhao; Sebastian Maurer-Stroh; Lit-Hsin Loo; Haiwei Song; Hao Fan (Archives of Toxicology, 2021)
Nuclear receptors (NRs) are key regulators of energy homeostasis, body development, and sexual reproduction. Xenobiotics binding to NRs may disrupt natural hormonal systems and induce undesired adverse effects in the body. However, many chemicals of concerns have limited or no experimental data on their potential or lack-of-potential endocrine-disrupting effects. Here, we propose a virtual screening method based on molecular docking for predicting potential endocrine-disrupting chemicals (EDCs) that bind to NRs. For 12 NRs, we systematically analyzed how multiple crystal structures can be used to distinguish actives and inactives found in previous high-throughput experiments. Our method is based on (i) consensus docking scores from multiple structures at a single functional state (agonist-bound or antagonist-bound), (ii) multiple functional states (agonist-bound and antagonist-bound), and (iii) multiple pockets (orthosteric site and alternative sites) of these NRs. We found that the consensus enrichment from multiple structures is better than or comparable to the best enrichment from a single structure. The discriminating power of this consensus strategy was further enhanced by a chemical similarity-weighted scoring scheme, yielding better or comparable enrichment for all studied NRs. Applying this optimized method, we screened 252 fatty acids against peroxisome proliferator-activated receptor gamma (PPARγ) and successfully identified 3 previously unknown fatty acids with Kd = 100–250 μM including two furan fatty acids: furannonanoic acid (FNA) and furanundecanoic acid (FUA), and one cyclopropane fatty acid: phytomonic acid (PTA). These results suggested that the proposed method can be used to rapidly screen and prioritize potential EDCs for further experimental evaluations.

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Profile and development of microsatellite primers for Acanthogobius ommaturus based on high-throughput sequencing technology - Chenyu Song; Ziyi Feng; Chunhou Li; Zhicheng Sun; Tianxiang Gao; Na Song; Lu Liu (Journal of Oceanology and Limnology, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

bHLH genes polymorphisms and their association with growth traits in the Pacific oyster Crassostrea gigas - Na Chen; Li Li; Chenghua Li; Zhihua Lin; Jie Meng; Sheng Liu; Kai Song; Yongbo Bao (Journal of Oceanology and Limnology, 2020)

The sweet sorghum SbWRKY50 is negatively involved in salt response by regulating ion homeostasis - Yushuang Song; Jinlu Li; Yi Sui; Guoliang Han; Yi Zhang; Shangjing Guo; Na Sui (Plant Molecular Biology, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Pedobacter indicus sp. nov., isolated from deep-sea sediment - Xiao-yan He; Na Li; Xiu-lan Chen; Yu-zhong Zhang; Xi-ying Zhang; Xiao-yan Song (Antonie van Leeuwenhoek, 2020)

Interactions between intercropped Avena sativa and Agropyron cristatum for nitrogen uptake - Min Liu; Huimin Li; Jingjing Song; Minghua Song; Na Qiao; Yuqiang Tian; Yanjie Liu; Haishan Niu (Plant and Soil, 2020)

The DI–DII linker of human parainfluenza virus type 3 fusion protein is critical for the virus - Ying Liu; Miaomiao Chi; Hongling Wen; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2020)

Shallow Genetic Structure of Pholis fangi in Bohai Sea and Yellow Sea Inferred from mtDNA Control Region - Tianxiang Gao; Lin Li; Rundong Fang; Guanghui Liu; Lei Wang; Hanxiang Xu; Na Song (Journal of Ocean University of China, 2019)

Water entry in jujube fruit and its relationship with cracking - Na Li; Lijiao Fu; Yuqin Song; Jie Li; Xiaofang Xue; Shuran Li; Liulin Li (Acta Physiologiae Plantarum, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

The Toxicological Effects of Mercury Exposure in Marine Fish - Na Zheng; Sujing Wang; Wu Dong; Xiuyi Hua; Yunyang Li; Xue Song; Qingwen Chu; Shengnan Hou; Yang Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Transcriptome analysis of 1- and 3-year-old Panax notoginseng roots and functional characterization of saponin biosynthetic genes DS and CYP716A47-like - Jian Li; Lan Ma; Shuting Zhang; Cailian Zuo; Na Song; Shusheng Zhu; Jinsong Wu (Planta, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

The Madden–Julian oscillation during the 2016 summer and its possible impact on rainfall in China - Xiaolu Shao; Shuanglin Li; Na Liu; Jie Song (International Journal of Climatology, 2018)
The summer rainfall in China in 2016 exhibited a substantial intraseasonal feature, with an intensification in June and July but a suppression in August over the Yangtze River Basin and North China. The Madden–Julian oscillation (MJO) during the summer and its impact on rainfall in China are investigated by conducting observational analyses and diagnostic linear baroclinic model (LBM) experiments. A significant MJO activity in the summer is observed with three MJO episodes corresponding to three stages of rainfall in China. The LBM is utilized to diagnose the circulation response to the tropical heating forcing associated with each MJO episode. The results suggest that much of the atmospheric circulation linked to the anomalous rainfall is attributed to the strong MJO episodes. During June–July (August), the enhanced (suppressed) convection over the tropical Indian Ocean along with the suppressed (enhanced) convection over the South China Sea (SCS) to the western Pacific excite an ‘East Asian–Pacific’ north‐eastward‐propagating Rossby wave train, inducing anomalous low‐level anticyclonic (cyclonic) flows over the northern SCS and the western North Pacific but cyclonic (anticyclonic) flows over North China. They lead to a westward (eastward) shift and strengthening (weakening) of the western Pacific subtropical high, thus favouring the intensification (suppression) in rainfall over the Yangtze River Basin and North China along with the opposite variation over South China. Relative to the first MJO episode, the MJO convection in the second episode causes a northward movement of the anomalous rainfall band from the Yangtze River Basin to North China. Apart from the impact on the above regions, the first (second and third) MJO episode favours an increase (reduction) in rainfall over Northeast China.

Fine-mapping and identifying candidate genes conferring resistance to Soybean mosaic virus strain SC20 in soybean - Adhimoolam Karthikeyan; Kai Li; Cui Li; Jinlong Yin; Na Li; Yunhua Yang; Yingpei Song; Rui Ren; Haijian Zhi; Junyi Gai (Theoretical and Applied Genetics, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Impact of IL-10-1082A/G gene polymorphism on the severity of EV71 infection in Chinese children - Qiubo Li; Hongfang He; Ya Guo; Yu Zhang; Peipei Liu; Yedan Liu; Chengqing Yang; Jie Song; Na Zhang; Zongbo Chen (Archives of Virology, 2018)

Special heterogeneous cytoplasm suppresses the expression of the gene producing multi-ovary in common wheat - Jialin Guo; Zheng Li; Gaisheng Zhang; Huali Tang; Qilu Song; Yulong Song; Shoucai Ma; Na Niu; Junwei Wang (Euphytica, 2017)

Complete mitochondrial genome of the Pleuronichthys lighti (Pleuronectiformes, Pleuronectidae) with phylogenetic consideration - Yaoxuan Song; Na Song; Yongdong Zhou; Pengfei Li; Shujiang Zhao; Tianxiang Gao (Genes & Genomics, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Resveratrol Inhibits Diabetic-Induced Müller Cells Apoptosis through MicroRNA-29b/Specificity Protein 1 Pathway - Kaihong Zeng; Yuan Wang; Na Yang; Duozi Wang; Suping Li; Jian Ming; Jing Wang; Xuemei Yu; Yi Song; Xue Zhou; Bo Deng; Xiaona Wu; et al. (Molecular Neurobiology, 2017)

Spatial and temporal changes in desertification in the southern region of the Tengger Desert from 1973 to 2009 - Qingyu Guan; Wenqian Guan; Jing Yang; Shilei Zhao; Baotian Pan; Lei Wang; Na Song; Min Lu; Fuchun Li (Theoretical and Applied Climatology, 2017)

Transcriptional sequencing and analysis of major genes involved in the adventitious root formation of mango cotyledon segments - Yun-He Li; Hong-Na Zhang; Qing-Song Wu; Gloria K. Muday (Planta, 2017)

New milbemycin metabolites from the genetically engineered strain Streptomyces bingchenggensis BCJ60 - Jian-Song Li; Min-Na Du; Hui Zhang; Ji Zhang; Shao-Yong Zhang; Hai-Yan Wang; An-Liang Chen; Ji-Dong Wang; Wen-Sheng Xiang (Natural Product Research, 2017)

“Turn-Off-On” Fluorescence Switching of Ascorbic Acid-Reductive Silver Nanoclusters: a Sensor for Ascorbic Acid and Arginine in Biological Fluids - Na Li; Yu He; Yili Ge; Gongwu Song (Journal of Fluorescence, 2017)

Heavy metals in the riverbed surface sediment of the Yellow River, China - Qingyu Guan; Ao Cai; Feifei Wang; Lei Wang; Tao Wu; Baotian Pan; Na Song; Fuchun Li; Min Lu (Environmental Science and Pollution Research, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

Inverse Association Between Serum Uric Acid Levels and Alzheimer’s Disease Risk - Na Du; Donghua Xu; Xu Hou; Xuejia Song; Cancan Liu; Ying Chen; Yangang Wang; Xin Li (Molecular Neurobiology, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Identification and genetic characterization of two porcine astroviruses from domestic piglets in China - Jin-song Li; Mao-zhong Li; Li-shu Zheng; Na Liu; Dan-di Li; Zhao-jun Duan (Archives of Virology, 2015)

Quantitative trait loci mapping of partial resistance to Diamondback moth in cabbage (Brassica oleracea L) - Nirala Ramchiary; Wenxing Pang; Van Dan Nguyen; Xiaonan Li; Su Ryun Choi; Ajay Kumar; Min Kwon; Hye Young Song; Shahnaz Begum; Mechuselie Kehie; Moo-Kyoung Yoon; Jonghyun Na; et al. (Theoretical and Applied Genetics, 2015)

Establishment and characterization of a gonad cell line from half-smooth tongue sole Cynoglossus semilaevis pseudomale - Ai Sun; Song-Lin Chen; Feng-Tao Gao; Hai-Long Li; Xiao-Feng Liu; Na Wang; Zhen-Xia Sha (Fish Physiology and Biochemistry, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

Effect of a New Kind of Liquid Fertilizer on Yield, Quality and Safety of Greenhouse Chinese Cabbage - Na Song; Juan Wang; Qunhui Wang; Jin Zheng; Jie Chen; Shanshan Shi; Fasheng Li (Agricultural Research, 2015)

Two new ionone glycosides from the roots of Rehmannia glutinosa Libosch. - Wei-Sheng Feng; Meng Li; Xiao-Ke Zheng; Na Zhang; Kai Song; Jian-Chao Wang; Hai-Xue Kuang (Natural Product Research, 2015)

An anther development F-box (ADF) protein regulated by tapetum degeneration retardation (TDR) controls rice anther development - Li Li; Yixing Li; Shufeng Song; Huafeng Deng; Na Li; Xiqin Fu; Guanghui Chen; Longping Yuan (Planta, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Glial Cell-Derived Neurotrophic Factor Attenuates Neuropathic Pain in a Mouse Model of Chronic Constriction Injury: Possible Involvement of E-cadherin/p120ctn Signaling - Cunjin Wang; Hongjun Wang; Jun Pang; Li Li; Suming Zhang; Ge Song; Na Li; Junping Cao; Licai Zhang (Journal of Molecular Neuroscience, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

M3 mAChR-mediated IL-8 expression through PKC/NF-κB signaling pathways - Zu-Peng Xu; Yun Song; Kai Yang; Wei Zhou; Li-Na Hou; Liang Zhu; Hong-Zhuan Chen; Yong-Yao Cui (Inflammation Research, 2014)

Non-esterified fatty acids activate the ROS–p38–p53/Nrf2 signaling pathway to induce bovine hepatocyte apoptosis in vitro - Yuxiang Song; Xinwei Li; Yu Li; Na Li; Xiaoxia Shi; Hongyan Ding; Yuhang Zhang; Xiaobing Li; Guowen Liu; Zhe Wang (Apoptosis, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

XRCC1 Arg399Gln genetic polymorphism and the risk of hepatocellular carcinoma: a meta-analysis - Yunpeng Qi; Lianhua Cui; Yang Song; Na Li (Molecular Biology Reports, 2014)

Biodegradation of high concentration of nitrobenzene by Pseudomonas corrugata embedded in peat-phosphate esterified polyvinyl alcohol - Na Liu; Hai-jun Li; Yue-e Shi; Bo-lin Zhu; Song Gao (World Journal of Microbiology and Biotechnology, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Glacial expansion and diversification of an East Asian montane bird, the green‐backed tit ( Parus monticolus ) - Wenjuan Wang; Bailey D. McKay; Chuanyin Dai; Na Zhao; Ruiying Zhang; Yanhua Qu; Gang Song; Shou‐Hsien Li; Wei Liang; Xiaojun Yang; Eric Pasquet; Fumin Lei (Journal of Biogeography, 2013)
Aim We combined genetic sequence data and ecological niche modelling to resolve the impacts of past climatic fluctuations on the distribution, genetic diversification, and demographic dynamics of an East Asian montane bird, the green‐backed tit ( Parus monticolus ). Location East Asia. Methods Phylogenetic analyses were carried out using four mitochondrial fragments and seven nuclear loci from 161 birds sampled from 29 localities spanning the entire geographical range of the green‐backed tit. We used * beast to estimate the species tree and calculate divergence times. Extended Bayesian skyline plots were used to infer potential historical shifts in population size. We used MaxEnt to predict potential distributions during three periods: the present day, the Last Glacial Maximum and the Last Interglacial. Results The mitochondrial DNA (mt DNA ) gene tree showed strong support for three reciprocally monophyletic groups: a south‐western clade, a central clade and a Taiwanese clade. Taiwanese and Vietnamese samples had fixed differences at several nuclear loci, but the south‐western and central samples shared haplotypes at all nuclear loci. The mt DNA gene tree topology differed from the species tree topology. The species tree suggested sister relationships between Taiwanese and Vietnamese operational taxonomic units ( OTU s) and between south‐western and central OTU s. Diversification within the green‐backed tit was relatively recent, probably within the last 0.9 million years. Extended Bayesian skyline plots suggested rapid population expansion in the south‐western and central phylogroups after the Last Interglacial, and this result was consistent with ecological niche models. Main conclusions Our results suggest that genetic diversification within the green‐backed tit was affected by the later Pleistocene climate fluctuations. Ecological niche models indicated that the present‐day vegetation distribution was, in many ways, more similar to that of the Last Glacial Maximum than it was to that of the Last Interglacial. Continental populations of the green‐backed tit experienced unusual demographic and range expansion that is likely to have occurred during the cooling transition between the Last Interglacial and the Last Glacial Maximum. We found incongruence between the mt DNA gene tree and the species tree, which underscores the importance of using both mitochondrial and nuclear markers when estimating the evolutionary history of populations.

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Tea consumption and risk of stroke: a dose-response meta-analysis of prospective studies - Li Shen; Liu-guang Song; Hong Ma; Chun-na Jin; Jian-an Wang; Mei-xiang Xiang (Journal of Zhejiang University-SCIENCE B, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Construction of a recombinant human FGF1 expression vector for mammary gland-specific expression in human breast cancer cells - Yang Zhou; Linzhu Ren; Jianguo Zhu; Sen Yan; Haijun Wang; Na Song; Li Li; Hongsheng Ouyang; Daxin Pang (Molecular and Cellular Biochemistry, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Changes in the trophic interactions and the community structure of Lake Taihu (China) ecosystem from the 1960s to 1990s - Yunkai Li; Bing Song; Yong Chen; Liqiao Chen; Na Yu; Derek Olson (Aquatic Ecology, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Long-Term Toxicity Effects of Cadmium and Lead on Bufo raddei Tadpoles - Yingmei Zhang; Dejun Huang; Dongqin Zhao; Jing Long; Gang Song; An’na Li (Bulletin of Environmental Contamination and Toxicology, 2007)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)